Calligraphy paintings in Malaysia: Clarification as an art tradition - Hamidon, N.A.; Md. Zain, D.H.; Bujang, R.; Janeri, M. (2011)
From the perspective of history and tradition, the art of calligraphy painting is seen to co-exist from two distinct traditions of the arts, that of the west and east traditions. Both traditions converge to form a new phenomenon via the assimilation process of the modern era. The phenomenon led to the formation of an art tradition - a premise both assumed and proven - wherein the form is indicative of the times seen in the light of conflicting cultural and ideological knowledge vis-a-vis the Islamic and secular values. However this phenomenon can be seen as an integrative element between various racial entities of early post-modern Malaysia for more than a decade. It also gave rise to the commitment of certain quarters to create a work of art that imbues the Islamic ideology, a reactive alternative to the variety of trends and art forms occurring in Malaysia then and generally viewed as lacking in art philosophy as compared to the Islamic Tawhid philosophy depicted in calligraphy paintings especially when associated with the holiness and preciseness of its meaning. To some artists, the art of calligraphy painting is a preferred choice because of the fulfillment in depicting mature and deep spiritual experience. All these observations led to the need to investigate the calligraphy art works in Malaysia more seriously in the form of a proper research endeavour, in order to enable its history as an art form be given due attention as one that is precise and able to promulgate the Malay national identity.